Developing Pure Cartoon for Stoichiometry Concept Combined with Guided Inquiry to Improve Process Skill and Students’ Learning Outcome - Hamid, Fatma Al (Universitas Negeri Malang, 2017)
Abstract: This research aims at improving processing skills and learning outcome of students on stoichiometry concept. First stage was instructional instrument development, the second stage was trials on X graders of Senior High School using One Group Pre-test and Post-test Design. The results of this research showed that (1) the developed instructional instrument is good and reliable, (2) the lesson plan was well-accomplished, (3) students activity were positive during the learning, (4) students response were positive, (5) the cognitive learning iutcomes of product and process have met minimum criteria of mastery learning, (6) the improvement of processing skill is in the category of high gain. To sum up, the developed instructional instrument could improve students processing skill and learning outcomes.Keyword: guided inquiry, learning outcomes, process skill, pure cartoonAbstrak: Penelitian ini bertujuan meningkatkan keterampilan proses dan hasil belajar siswa pada konsep stoikiometri. Tahap pertama adalah pengembangan perangkat pembelajaran, tahap kedua adalah ujicoba pada siswa kelas X SMA menggunakan One Group Pre-test and Post-test Design. Hasil penelitian menunjukkan : 1. perangkat pembelajaran berkategori baik dan reliabel, 2. RPP dapat terlaksana dengan baik, 3. aktivitas siswa sangat positif dalam pembelajaran, 4. respon siswa terhadap pembelajaran sangat positif, 5. hasil belajar kognitif produk dan proses menunjukkan ketuntasan KKM; 6. peningkatan keterampilan proses berada pada kategori high gain. Hasil penelitian menunjukkan bahwa media yang dikembangkan dapat meningkatkan keterampilan proses dan hasil belajar siswa.Kata kunci: hasil belajar, inkuiri terbimbing, keterampilan proses, pure cartoon